Flourishing of Occidentalism in Iran After Cultural Revolution - Shalaleh ZABARDAST (Gazi Akademik Bakış)
Modernity changed the community interests; it idealized individuality and liberal democracy, and based its main aim on pushing religion to the outskirts of human life. Western Christianity adjusted to modernity to justify the developments while Islam accepted it only to the extent of its capacity to authenticate the realities stated by the Qur’an. Orientalism, Occidentalism, and Islamism play impressive role in a variety of contexts today. Occidentalism in its popular variety helps to reinforce the identities. This study considers the power relationship between people and cultures. The roles and the identities are changing throughout history. Nowadays Islamic culture is one of popular subjects to study on. So, the Muslim world and revival of Islamic culture are the beginning of Occidentalism. Occidentalism is developed in the Orient in order to study the West from a non-Western World point of view. It can be referred as revival of identity (for isteghrab) in Arab world by Hasan Hanafi or Talibanian or ISIS Occidentalists movements which stand for empowering Arab culture, Wahhabism or Salafism. All are revivalist movements to rapture Islamism as an ideology. This article tries to focus on the concept of Occidentalism in Iran after Iran Cultural Revolution.